Optimization of process parameters in TIG welding of AISI 4140 stainless steel using Taguchi technique. (2021) - Natrayan, L.; Anand, R.; Santhosh Kumar, S.
Abstract: Tungsten inert gas (TIG) welding is a fusion welding technology with a wide variety of uses in the modern industry. TIG welding process parameters act as significant influences to evaluate the quality of the welded joint. In this research, the optimization technique for Tungsten inert gas process parameter is established by the Taguchi technique to explore the tensile strength of AISI 4140 stainless steel welded joint. Three different welding process parameters such as welding current, welding speed and filler diameter have selected to perform the experiments using L9 orthogonal array. The regression model was used to establish a relationship between welding input parameters and penetration for Tungsten Inert Gas welding of AISI 4140 stainless steel plates. The optimal process parameter for tensile strength conclude welding current at level 1 (A1), weld speed at level 3 (B3), filler diameter at level 3 (C3). ANOVA results exposed that welding Speed is the highest contributor for achieving the tensile strength.